Penyegaran Tentang Metode Penelitian Ilmiah Untuk Widyaiswara - Yuliana Ria Uli Sitanggang (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2019)
Producing a scientific article is one of the requirements that must be met by the Widyaiswara (civil servants who are responsible for doing education and training for other civil servas) to be able achieve higher level of rank and positions. This paper is intended to motivate the Widyaiswara in conducting scientific research. This article briefly discusses about the relevance of knowledge and research, the research processes, the hypothetical example of scientific research and scientific research ethics.